Le rôle de la Guyane précolombienne dans la zone d’interactions caribéo-amazonienne - Gérald Migeon (EchoGéo)
After a short synthesis o the cultural evolution of the precolumbian civilizations of French Guyana, and particularly of the coast of Guyana, from 10000 years ago to the Conquest, the autor examines, in the first place, the relationships between French Guyana, Brazil and others Guyanas, the roads and the motivations of this interrelationships (after the period of the hunters-gatherers), and describes emphasizing three types of artefacts the interrelationships into or between the Guyanas.